Effects of window opening style on inside environment of solar greenhouse based on CFD simulation - Sun, Yachen; Bao, Encai; Zhu, Chenmeng; Yan, Lulu; Cao, Yanfei; Zhang, Xuanhe; Li, Jianming; Jing, Haiwei; Zou, Zhirong (International Journal of Agricultural and Biological Engineering, 2020)
Solar greenhouse is extensively used in horticultural production in China. Natural ventilation is one of the key technological means to adjust the inside environment of greenhouse, while the effects of window opening styles on the inside environment are still not well understood. In the present study, the temperature and air flow field of five operation styles, namely back roof central opening style (G1), back roof evenly spaced opening style (G2), top roof full opening style (G3), style of G1+G3, and style of G2+G3 were simulated using the CFD method. The results indicated that: (1) the simulated and measured results exhibited favorable agreement, with relative errors within 5%; (2) In the case of the windows opening area was the same and only single ventilation style was applied, back roof full opening style exhibited the best cooling effect. The inside average temperature of the greenhouse with G1 style decreased by 0.5°C and 1.6°C respectively compared with those of greenhouses with G2 and G3. (3) The cooling effect of the style of G2+G3 was more favorable than that of the style of G1+G3. The style of G2+G3 exhibited better cooling effect than the single ventilation styles, with the lowest temperature (27.5°C) and temperature uniformity coefficient (0.36).Keywords: CFD modeling, window opening styles, cooling effects, solar greenhouseDOI: 10.25165/j.ijabe.20201306.5734Citation: Sun Y C, Bao E C, Zhu C M, Yan L L, Cao Y F, Zhang X H, et al. Effects of window opening style on inside environment of solar greenhouse based on CFD simulation. Int J Agric & Biol Eng, 2020; 13(6): 53–59.